Maintenance plan model to increase truck availability rate by applying 5S, TPM and Kanban in the construction sector - Camacho - Ubillus, Rodolfo (2023)
Companies in different industries have been searching for alternatives that allow them to build a strategy that can lead to positive results. The implementation of the 5S tool aims to maximise efficiency and speed up the work of employees; unnecessary movements were eliminated by placing tools and equipment in the right position, clearly visible, clean and available. The development of the Total Productive Maintenance tool focused on three pillars: autonomous maintenance 'AM', planned maintenance 'PM' and training and coaching. As a last tool, kanban was applied, which consists of stock control of spare parts through coloured cards. In the present research work, the availability rate of the units in the construction sector was increased from 75% to 90% of the mechanical availability by means of the 5S, TPM and KANBAN tools.